Intumescent polypropylene: Reaction to fire and mechanistic aspects. (April 2019) - Bourbigot, Serge; Sarazin, Johan; Bensabath, Tsilla; Samyn, Fabienne; Jimenez, Maude
Abstract: The concept of intumescence was applied to make flame retarded polypropylene (PP). This paper examines two types of intumescence in PP based on expandable graphite (EG, physical expansion) and on modified ammonium polyphosphate (AP760, chemical expansion). Reaction to fire of PP containing EG and AP760 was first evaluated by cone calorimetry. The incorporation of intumescent additives at relatively low loading (10 wt%) in PP permits the reduction by 70% of peak of heat release rate (pHRR). The mode of action occurs via the formation of an expanded carbonaceous layer in all cases. The protective coating acts mainly as heat barrier in the case of the formulations containing AP760 or as heat dissipater with EG. The incorporation of small amount of EG in PP-AP760 modifies heat transfer in the coating creating a strong anisotropy. Upon expansion, graphite worms align normal to the surface increasing the transverse heat conductivity (lower efficiency of the heat barrier) and hence, decreasing the fire performance (decrease by only 30% of pHRR). Kinetic analysis was then performed to quantify the thermal stability of the intumescent systems. It reveals that the intumescent additives do not modify the reactional scheme of the PP thermal decomposition but they increase slightly the thermal stability of the intumescent systems. For all materials, the decomposition model follows a reactional scheme at two successive reactions. This model was determined in dynamic conditions (conditions of thermogravimetry with linear heating rates) but it is able to simulate the decomposition of the materials in isothermal conditions (excellent agreement between the simulated and experimental curves). Graphical abstract: Image 1 Highlights: 70% of HRR reduction using only 10 wt% intumescent additive in polypropylene. Worms of EG (physical expansion) come up normal to the surface when combined with APP-based additive (chemical expansion). Worms of expandable graphite create high anisotropic heat conductivity. X-ray tomography reveals the inner part of intumescent chars.